In vitro study of the preventive activity of fluoride varnish by X-ray diffraction - Dobrinka Mitkova Damyanova; Siyana Georgieva Atanasova (International Journal of Public Health Science (IJPHS), 2023)
In exogenous prophylaxis, fluoride is applied directly to the tooth surface through various gels, varnishes, foams, and toothpaste. According to the global burden of disease study conducted in 2017, more than 530 million children worldwide suffer from dental caries in their primary dentition. There are few developments in the selection of non-invasive methods in the application of mineralizing varnishes. The researchers investigated experimentally, in-vitro the preventive activity of the fluoride varnish Clinpro™ White Varnish with TCP 3M (CV), using a modern method of X-ray diffraction. The 20 temporary teeth were extracted due to physiological changes. Place of study was UMDC - city of Varna and Institute of Physical Chemistry "Academician Rostislav Kaishev" of the Bulgarian Academy of Sciences, Sofia. Demineralization is carried out with 37% phosphoric acid (i-gel – etching gel) and applied to the smooth temporary enamel surfaces for 30 seconds. The models were then washed and dried with a water and air jet. Remineralization was performed with CV. The formation of small globules of calcium fluoride. The coating is composed mainly of fluorapatite. With the modern method of X-ray diffraction, it was proved that exogenous fluoride prophylaxis and remineralization therapy are effective methods of prevention and treatment of initial caries lesions.